Tata Laksana ‘Behavioral Activation’ untuk Menurunkan Tingkat Depresi pada Pasien Stroke - Ima Santika Jayati; M. Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2015)
Depression in patients of stroke causes a decrease in health, quality of life, and positive feelings. Behavioral Activation (BA) is a technique that consists of various series of activities that can increase happiness, productivity, and patient's meaning of life. BA for depression in stroke patients still needs to be developed more in clinical setting. Therefore, we need a treatment guideline for psychologists in conducting assessment, diagnosis, and treatment for depression in stroke patients based on BA principles. This study aims to verify the effectiveness of BA guideline by evaluating psychologist’s self efficacy in delivering service for stroke patients, patients’ satisfaction of service, & patients’ BDI scores. Data were analyzed by visual inspection and qualitative analysis.